The Determinants of Capital Structure on Property and Real Estate Company Period 2012-2016 - Ranitasari, Rani; Maftukhah, Ida (Universitas Negeri Semarang, 2018)
The research aims to know the determinant of capital structure. Population in this research is property and real estate company listed in Indonesia Stock Exchange period 2012-2016. The sample in this research is determined based on purposive sampling which is sampling technique based on certain criteria. Companies that meet the criteria of the sample are 30 companies with research period during 4 years, so obtained the data of 150 observations. The analysis used was multiple linear regression analysis which was preceded by panel data model selection and classical assumption test. The result of random effect model regression test shows that profitability and liquidity have significant negative effect on capital structure, while asset growth has significant positive effect on capital structure, but the firm size and asset structure had no significant positive effect on capital structure.